TINJAUAN HUKUM SENGKETA ANJAK PIUTANG (PUTUSAN PENGADILAN NEGERI MALANG NOMOR 283/Pdt.Bth/2023): Legal Review of Factoring Disputes (Malang District Court Decision Number 283/Pdt.Bth/2023) - Muhammad Arfan Hakim (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This article analyzes the Malang District Court Decision Number 283/Pdt.Bth/2023 concerning a factoring (cession) dispute. The case focuses on the validity of the cession deed, particularly regarding its formal and material requirements, and the obligation to notify the debtor as stipulated in Article 613 of the Civil Code. Furthermore, this case involves the interests of a third party, a bank, which holds collateral rights over the receivables. This research uses a normative juridical method with a case study approach, based on an analysis of norms, doctrine, and court decisions. The results indicate that the primary legal debate lies in the validity of the cession and its legal consequences for the debtor, new creditors, and good-faith third parties. This decision holds significant significance as a jurisprudential precedent in the practice of receivables-transfer-based financing, particularly in the context of debtor protection and legal certainty.